Coalition Formation by Male Vervet Monkeys (Chlorocebus pygerythrus) in South Africa. (January 2016) - Freeman, Natalie J.; Young, Christopher; Barrett, Louise; Henzi, S. Peter
Abstract: Unrelated male primates frequently cohabit in bisexual groups and, despite being reproductive competitors, have been shown to cooperate in ways that are associated with reproductive success. Such coalitions between males are common in some taxa, where they can serve two primary functions – status management and improved mating opportunities – that subserve long‐ and short‐term objectives. Here, we use observational data to provide information on male coalitions in vervet monkeys ( Chlorocebus pygerythrus ), a guenon with a multimale group structure. We recorded a total of 62 coalitions from two troops across a 10‐mo period at Samara Game Reserve, South Africa. We found that males who were more frequently associated spatially and who had groomed one another were more likely to form coalitions and did so against higher‐ranking opponents. This was not linked to any evidence that coalitionary aggression provided either short‐ or long‐term reproductive benefits for the aggressors and coalitions were not restricted to the mating season. There was little evidence that particular individuals were targeted, reciprocation between partners was not observed, and recent immigrant males were not targeted disproportionately. Our data suggest that within‐group coalition formation between vervet males may represent something close to an ancestral state whereby males form ad hoc coalitions opportunistically, joining an ongoing dyadic contest to target an opponent without facing the possible risks of dyadic contest, such as a greater chance of injury.